Teaching culture in the FL senior high school classroom. Coursebook evaluation and teachers’ and learners’ views - Derenowski, Marek (Wydawnictwo Naukowe UAM, 2015)
W książce podjęto próbę zdefiniowania miejsca kultury języka angielskiego w klasie językowej oraz opisano proces nauczania kultury w kontekście szkoły ponadgimnazjalnej. Pierwsze dwa rozdziały zawierają informacje na temat pojęcia kultury, jej postrzegania w różnych naukach społecznych oraz edukacji interkulturowej, a także wybranych narzędzi i technik do rozwijania kompetencji interkulturowej uczniów. Ostatni rozdział przedstawia trzy badania empiryczne mające na celu uzyskanie wiarygodnych danych na temat wykorzystania elementów kulturowych w nauczaniu języka angielskiego, a także na temat procesu rozwijania kompetencji interkulturowej uczniów. Monografia jest efektem doświadczeń i przemyśleń autora, a także jego rozmów i obserwacji codziennej pracy nauczycieli, którzy często zaniedbują nauczanie kultury, przekonani, że w klasie językowej jest miejsce tylko na jedno: nauczanie kultury albo sprawności językowych.

Teaching culture in the FL senior high school classroom: Coursebook evaluation and teachers' and learners' views makes an attempt to define the place of target language culture in the foreign language classroom as well as describes the development of cultural knowledge in the senior high school context. The first two chapters include information concerning the perception of 'culture' in various social sciences, intercultural education, and selected techniques and tool used while developing learners' cultural knowledge. The last chapter contains descriptions of three empirical studies, which aim was to gather credible data about the incorporation of target language culture elements in the English language classroom. The book is the outcome of the author's experience, reflections, discussions, and observations of teachers' everyday work. Teachers often neglect teaching culture convinced that in the foreign language classroom there is only a place for one, culture or language skills.
Keywords: edukacja interkulturowa; kultura języka angielskiego